Science Education In South-West Nigeria: Implications For Educational Policy - Ayodeji M. Adebayo; Olutoyin O. Sekoni; Scholastica N. Lan; Oladoyin M. Odubanjo; Oluwaseun O Akinyemi; Taiwo A Obembe; Anjolaoluwa O. Olanipekun; Kayode O. Osungbade; Akinyinka O. Omigbodun (The Proceedings of the Nigerian Academy of Science, 2018)
The demand for quality science education requires periodic assessment for its improvement especially in areas with previous challenges. This study was conducted to assess the current status of science education in Ekiti State, Southwest Nigeria. A cross-sectional design, combining a mixed method of quantitative and qualitative data collection approach, was used following a records review. Schools were selected using a cluster sampling technique. Science education status was ascertained by three parameters: students’ pass rates in science subjects in the Senior Secondary School Certificate Examination, science teachers’ profile (assessed with a 14-item self-administered questionnaire) and availability and functionality of infrastructure for science education using an observational checklist. In-depth interviews were conducted among relevant stakeholders using an in-depth interview guide. Quantitative and qualitative data were analyzed with descriptive statistics and a thematic approach respectively. Students’ pass rates were below 50% in Mathematics and Biology but above in Physics, Chemistry and Agricultural Science. The science teacher: student ratio was 1:8 and 37.5% of the teachers were members of the Nigerian Science Teachers Association. One school (8.3%) had a computer library that was adequately equipped. Laboratory facilities were mostly multipurpose in nature. A quarter of the schools had no library while 33.3% had grossly inadequate library facilities. Opinions about science education status among the respondents was widely divergent with some feeling that it was good while others felt otherwise. This study revealed poor status of science education as evidenced by a low science teacher-student ratio and lack of basic infrastructure for science education. Interventions to improve these findings are recommended.